Development of Parabolic Concentrator-Based Thermoelectric Generator - Siti Nor Aisyah, Burhanudin; Amir Izzani, Mohamed; Zainor Afezi, Zainal Abidin; Mohd Shawal, Jadin (2017)
Thermoelectric generator (TEG) is one of the solutions to produce energy from waste heat and produce pure DC voltage. TEG is based on solid state technology with no moving parts and works on the principle of Seebeck effect. In this work, TEG was combined with a solar concentrator to produce a device that able to convert solar energy to electrical energy. The concentrator was used to concentrate thermal energy from the sun onto one side of the thermoelectric module which acts as the hot side. The assembled system is able to produce maximum power output up to 0.157W with 0.479% of an efficiency achieved.